2015 Nepal Earthquake: Analysis of Child Rescue and Treatment by a Field Hospital. (18th May 2016) - Wang, Jun; Ding, Hui; Lv, Qi; Chen, Jin-hong; Sun, Yan-feng; Fan, Hao-jun; Liu, Qiu-ling
Abstract: Objective: To retrospectively analyze the rescue and treatment of pediatric patients by the Chinese Red Cross medical team during the Nepal earthquake relief. Methods: The medical team set up a field hospital; the pediatric clinic consisted of 1 pediatrician and several nurses. Children younger than 18 years old were placed in the pediatric clinic for injury examination and treatment. Results: During the 7-day period of medical assistance (the second to third week after the earthquake), a total of 108 pediatric patients were diagnosed and treated, accounting for 2.8% of the total patients. The earthquake-related injuries mainly required surgical dressing and debridement. No severe limb fractures or traumatic brain injuries were found. Infection of the respiratory tract, the gastrointestinal tract, and the skin were the most common ailments, accounting for 42.3%, 18.5%, and 16.7%, respectively, of the total treated patients. Conclusion: Two to 3 weeks after the earthquake, the admitted pediatric patients mainly displayed respiratory and gastrointestinal infections. When developing a rescue plan and arranging medical resources, we should consider the necessity of treating non–disaster-related conditions. ( Disaster Med Public Health Preparedness . 2016;page 1 of 4)